Design of an optimised preamplifier for the MRPC detector - Li, Yulan; Yue, Xiaoguang; Zeng, M.; Cang, J.; Li, Z.; Wang, Y.; Yu, Y. (Journal of Instrumentation, 2020)
Multi-gap Resistive Plate Chamber (MRPC) is widely used in many major international projects as an important element of the Time-of-flight (TOF) system because of its high time resolution. The typical time resolution of a MRPC system is about 60 ps, while the intrinsic time resolution of the MRPC detector can be smaller than 20 ps. This paper aims to improve the time resolution preformance of a 32-gap, 104 mu m-thick MRPC system by optimising the readout electronics, which consists of a current mirror (CM) and a modified transimpedance amplifier (TIA). A nominal time resolution of 11.37 ps can be achieved for a MRPC detector with a delta current signal input and a charge of around 34 fC according to a MATLAB simulation. The MRPC system using this preamplifier can achieve a time resolution of 27 ps combining with high-speed waveform sampling method.
Gesehen am 27.05.2020